2022
DOI: 10.1101/2022.01.14.476337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-use of labware reduces CO2 equivalent footprint and running costs in laboratories

Abstract: Laboratory-based research is resource intensive in terms of financial costs and carbon footprint. Research laboratories require immense amounts of energy to power equipment and material, particularly of single-use item consumption. Reliance on single-use plastics within laboratories. Understanding the full carbon footprint of consumable usage is increasingly important as many research institutes commit to carbon neutrality. To date, no carbon footprint assessment has been conducted to detail the differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…We found that air drying of ethidium bromide gels before disposal reduces their weight by >95%, which decreased our amount of toxic waste by up to 80%. Reduce plastic waste by planning your experiments well, replacing single‐use plastics with glassware, and reusing plastic where possible (Bowler, 2022 ; preprint: Farley & Nicolet, 2022 ). Some producers also offer to take back their used consumables (e.g., tissue culture media bottles, pipette tip boxes, and gloves).…”
Section: The Paradoxmentioning
confidence: 99%
“…We found that air drying of ethidium bromide gels before disposal reduces their weight by >95%, which decreased our amount of toxic waste by up to 80%. Reduce plastic waste by planning your experiments well, replacing single‐use plastics with glassware, and reusing plastic where possible (Bowler, 2022 ; preprint: Farley & Nicolet, 2022 ). Some producers also offer to take back their used consumables (e.g., tissue culture media bottles, pipette tip boxes, and gloves).…”
Section: The Paradoxmentioning
confidence: 99%
“…A selection of the many resources available to learn about environmental issues and sustainable science 1‐3 , 5‐7 , 9‐10 , 15‐20 , 22 , 24‐29 , 32‐58 , 64 , 67‐69 , 74‐76 , 81‐82 . This figure was created using BioRender.com.…”
Section: Become Informedmentioning
confidence: 99%
“…(2) documentaries 35-37 ; (3) podcasts 38,39 ; (4) books [40][41][42][43][44][45][46][47][48][49][50][51] and even thoughtprovoking fictional works. 52 A range of excellent courses and training opportunities are also available, A growing collection of resources is also available to learn more about sustainability in a scientific setting, including reports 26 and articles on sustainable science, 18,19,20,24,27,53 waste in laboratories, [54][55][56] greener computing 57 and sustainable conferencing. 58 Many of these issues are also covered on The Caring Scientist: Mission Sustainable podcast.…”
Section: Become Informedmentioning
confidence: 99%
“…Such reduction was of the same order but smaller than that computed at the single laboratory scale. 42 The magnitude of this decrease is a function of the proportion of disposable plastic consumables in purchases emissions and can reach up to −5.6 ± 4.5 % for a LHS laboratory for which this type of purchases represented ∼ 8 % of purchases footprint. At last, efficiency and sufficiency measures resulting in a 2-fold reduction in the purchases of scientific consumables (MS6) resulted in a 5.9 ± 4.7 % and a 9.7 ± 7.8 % decrease in the total footprint of ST and LHS laboratories, respectively.…”
Section: The Typology Of Purchases Emissions Depend On Research Domainmentioning
confidence: 99%